Liquid biopsy in orthopedic trauma: exosomes as functional mediators and mechanistic indicators in post-traumatic complications - Gan, Jinyu; Zhong, Shuangting; Xie, Juan; Zou, Liqun (Frontiers in Medicine, 2025)
Severe orthopedic trauma initiates complex pathophysiological cascades that frequently lead to life-threatening complications including acute compartment syndrome, fat embolism syndrome, deep vein thrombosis, and fracture non-union. Traditional biomarkers provide only retrospective indicators of tissue damage, lacking the sensitivity and specificity needed for early complication detection. Exosomes, nanoscale extracellular vesicles carrying proteins, lipids, and nucleic acids, have emerged as critical mediators of intercellular communication that actively participate in trauma pathophysiology. This comprehensive review synthesizes accumulating evidence suggesting that exosomes may function as active mediators rather than passive biomarkers in orthopedic trauma complications. Studies demonstrate that trauma-derived exosomes transfer functional cargo including miR-155 and inflammatory proteins that reprogram recipient cell phenotypes and induce endothelial dysfunction. In vivo animal models show that mesenchymal stem cell-derived exosomes significantly enhance fracture healing in non-union models. Based on these findings, we present mechanistic models illustrating how trauma-induced exosomes may drive disease progression in each major complication through distinct molecular pathways. Furthermore, we discuss the diagnostic potential of exosomal biomarkers, address current methodological challenges, and outline future research directions for clinical translation. The integration of exosome-based approaches into trauma care represents a paradigm shift that could enable early detection of complications and development of targeted therapeutic interventions, ultimately improving patient outcomes through precision medicine.